Implementasi Hukum dalam Konteks Sosial dan Budaya yang Berbeda di Masyarakat - Rayhan Zaki Wibowo; Raden Roro Iska Sabrina Putri; Dyah Liesna Kusuma Wardani; Gilbert Christian Kaban; Her Dianta Mehaga Sebayang; Ariq Naufal Attalah Suhanda; Mulyadi M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study discusses the relationship between law and society. The aim of this research is to understand how law and society influence each other in different social and cultural contexts. The research method used is literature study and data analysis. The results of the study show that the implementation of law in society can be complex due to differences in cultural values, customs, religions and prevailing norms. Law plays an important role in shaping the social order of society, providing protection, and upholding values that are considered important. However, the implementation of unfair laws can trigger social dissatisfaction and conflict in society. Therefore, the implementation of law must take into account the various perspectives of society and seek the right balance between individual interests and public interests.